E-cigarette or vaping induced lung injury: A case series and literature review. (2020) - Doukas, Sotirios G.; Kavali, Leena; Menon, Rohan S.; Izotov, Boris N.; Bukhari, Amar
Highlights: 80 % of EVALI patients presented with respiratory symptoms. 60 % of the EVALI patients presented with gastrointestinal symptoms. All of the EVALI patients had ground glass opacities on chest imaging. Standardization of vaping history in both out-patient is highly recommended. Abstract: Introduction: Recently, a rapidly increasing number of e-cigarette or vaping induced lung injury (EVALI) has been reported across the nation. Given the ongoing epidemic, it has been suggested that specific chemical substances used as additives in e-cigarettes could be highly related to EVALI. A history of vaping with positive radiographic changes and low suspicion for active infection are requirements for diagnosis but it still remains a diagnosis of exclusion. The course of the disease, mechanism of lung injury and the optimal management options need to be better understood. Here we aimed to discuss the clinical characteristics recognized in a case series of ten hospitalized EVALI patients with radiological findings of lung injury and provide an up today summary of the known literature of EVALI-induced lung injury. Methods: A retrospective chart review was conducted on ten patients who presented to Saint Peter's University Hospital in New Brunswick, NJ from July 2019 to February 2020, with a mean hospital stay of five days. According to the CDC recommended definition of the disease, our cases met the current working definition of confirmed or probable cases of EVALI. Results: Ten patients, with mean age 30.8 years (50 % male) and average years of vaping 1.708 with 60 % endorsing a simultaneous history of cannabis-related products use, went under a retrospective review. 3/10 (30 %) had documented medically-managed pulmonary disease history, 8/10 (80 %) presented with the respiratory-related chief complaint, 6/10 (60 %) presented with gastrointestinal symptoms and 7/10 (70 %) had constitutional symptoms. All patients (100 %) were found to have bilateral ground-glass opacities on chest imaging. 9/10 were admitted, 6/10 (60 %) had an oxygen saturation of <95 % requiring oxygen supplementation with 4/10 managed in the intensive care unit. Conclusion: EVALI patients with radiological findings of lung injury, although mainly present respiratory symptoms, may very often appear with constitutional and gastrointestinal symptoms. Based on the existing literature and our data it is argued that EVALI may be misdiagnosed and that closer monitoring is required to determine optimal diagnostic and therapeutic management of this condition. Our data and the existing literature suggest that laboratory and epidemiologic findings can be contributory for the diagnosis of the disease.